Abraham Lincoln - Blashfield, Jean F. (Minneapolis, Minn. : Compass Point Books, 2002)
Depicts the life of Lincoln, surveys his political career, and discusses his accomplishments as president
To save the Nation -- The early years -- Stepping into politics -- The slavery debates -- The Civil War -- For the people -- Glossary -- Abraham Lincoln's life at a glance -- Abraham Lincoln's life and times -- Understanding Abraham Lincoln and his presidency -- The U.S. Presidents.
Includes bibliographical references and index.
8 - 10 years
Keywords: Lincoln, Abraham -- 1809-1865; Presidents -- United States -- Biography -- Juvenile literature; Presidents